Shattered Dreams and Stolen Childhood: A Study of Child Labour and Child Rights in Restaurants and Hotels of Pokhara, Nepal - Upadhyay, Prakash (Janapriya Journal of Interdisciplinary Studies, 2019)
Nepal is committed to end child labour expressed by the ratification of ILO convention and its national plan of action for children and Master Plan to end child labour. However, the wicked problem’ of child labour is increasing at an alarming rate in urban areas. New hotels and restaurants have been opened and along with it a new way of child labour exploitation has emerged in urban centres. Most of the workers in restaurants/hotels of Pokhara are children. The employers of such business prefer child labour as they are cheap and can be easily exploited. This study attempts to determine the extent to which child labour constitutes a violation of child rights. Pedestal on theories of exploitation and structural-functionalism the study result reveals that condition of child labourers is disgraceful with a shattered dream and stolen childhood—a result of family dysfunction and child rights violation by employer that has thwarted the opportunities for healthy adulthood under a vicious cycle of deprivation, abuse and exploitation. Amid noxious relationship between child labourer and the employer, child labourers face violence and sexual harassment by employer, senior staff and customers. Heavy workload, trouncing and dragging by hair and ill-treatment are the common violence faced by child labourer. Most of the employers are ignorant of child rights. It is a paradox that child labourer is valuable for employer but the life of child labourer is worthless. Most of the child labourers are willing to rehabilitate.